Impact of closed sabo dams on manganese concentration change in mountainous streams. Issue 1 (2nd January 2017) - Praise, Susan; Watanabe, Toru; Watanabe, Kazuya; Ito, Hiroaki; Okubo, Hiroshi
ABSTRACT: 'Sabo' dams are common features in the mountainous areas of Japan. Their major importance is to reduce the impact caused by occasional natural disasters. However, the existence of sabo dams may alter streams process such as the geochemical behaviour of organic and inorganic materials. Elevated retention and accumulation of sediments affect cycling of important elements such as iron and manganese (Mn). Organic matter is buried in layered patterns of soil textures beneath and alongside the streams. Such conditions bring change in redox conditions together with anaerobic decomposition, which affects the biogeochemical behaviour of various elements including Mn. In this study, the impact of closed sabo dams on the geochemical behaviour of Mn was investigated. Using the formaldoxime method, Mn concentration in sabo-dammed streams was determined. The results showed an increase in Mn concentration in the downstream of closed sabo dams with the highest increase of 276% in August 2012. Mn concentration varied in the range of 0.14 to <0.01 mg/l and it was retaliated to the season and dam location. Changes of Mn concentration in sabo dams were noted in all sites investigated. Mn concentration increased after sabo dams depending on the time of sampling, indicating reduction of Mn oxide/hydroxides within the closed sabo dams.